MY SAY: The politics of karma - Abd Razak, Dzulkifli (2009)
Last year, when a Hollywood celebrity tried to relate a major earthquake to the state of karma (simply put: you reap what you sow), she was heavily criticised. Some demanded an apology. How dare an AngloSaxon speak about something that she does not know much about. The disaster is a phenomenon of nature, so what has karma got to do with it, argued some. The mood was unforgiving. One comment simply read: "Shut up, shameless woman." So, when I chanced upon a commentary entitled "Blame our karma for our predicament", 1 was naturally curious. How so this time? That it was written by a nonAnglo Saxon woman — probably Buddhist, going by the name — made me even more curious.